Report on laboratory tests of sandstone and porphyry for rock fracture analysis - Jakub Gontarz; Jacek Szulej (Budownictwo i Architektura, 2020)
The paper presents the results of mechanical tests of three types of rocks from stone mines in Poland. Compression tests of cubic samples, three-point bending tests of beams, bending of beams with notch and testing of tensile strength using the quasi-Brazilian method were performed. Based on the tests, the compressive strength, tensile strength, Young's modulus, and Poisson's ratios were determined. The stress intensity factor and critical strain energy release rate in mode I were determined from the bending test of the notched beams. The determined values were used as parameters of computer models which are used to verify the authors’ method of predicting the crack propagation in the Abaqus FEA system.